2018
DOI: 10.3389/fimmu.2018.00193
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcing the Functionality of Mononuclear Phagocyte System to Control Tuberculosis

Abstract: The mononuclear phagocyte system (MPS) constitutes dendritic cells, monocytes, and macrophages. This system contributes to various functions that are essential for maintaining homeostasis, activation of innate immunity, and bridging it with the adaptive immunity. Consequently, MPS is highly important in bolstering immunity against the pathogens. However, MPS is the frontline cells in destroying Mycobacterium tuberculosis (Mtb), yet the bacterium prefers to reside in the hostile environment of macrophages. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 166 publications
(171 reference statements)
0
31
0
3
Order By: Relevance
“…Nevertheless, inflammatory monocytes can also play a deleterious effect by fueling and perpetuating the inflammatory response leading to unrestricted control of microbial infection and tissue pathology (Shi and Pamer, 2011;Pahari et al, 2018;Sampath et al, 2018). Our group and others have reported phenotypic and functional alterations in monocytes from TB patients compared to healthy controls (Sanchez et al, 2006;Balboa et al, 2011;Castaño et al, 2011a,b;Lastrucci et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Nevertheless, inflammatory monocytes can also play a deleterious effect by fueling and perpetuating the inflammatory response leading to unrestricted control of microbial infection and tissue pathology (Shi and Pamer, 2011;Pahari et al, 2018;Sampath et al, 2018). Our group and others have reported phenotypic and functional alterations in monocytes from TB patients compared to healthy controls (Sanchez et al, 2006;Balboa et al, 2011;Castaño et al, 2011a,b;Lastrucci et al, 2015).…”
Section: Discussionmentioning
confidence: 63%
“…Monocytes have been described as playing a dual role during Mtb infection. They are essential in the anti-mycobacterial defense through innate activation mechanisms and triggering the acquired immunity against Mtb; however, they may also participate in pathogen dissemination, inflammatory reaction, and the tissue damage occurring during TB (Pahari et al, 2018). It has reported that circulating monocytes from patients with pulmonary tuberculosis (TB) exhibit phenotypic and functional alterations compared with healthy controls (Sanchez et al, 2006;Castaño et al, 2011a;Chavez-Galan et al, 2015), which can be associated with disease progression or severity.…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages play a pivotal role in the activation as well as differentiation of naïve CD4 T cells [ 2 , 7 ]. Next, we explored the ability of AcrMΦpre and AcrMΦpost treated macrophages to activate T cells.…”
Section: Resultsmentioning
confidence: 99%
“…It is of paramount importance to comprehend the intricate host–pathogen interaction and the evasion approaches thrived by M . tb to circumvent immune onslaught of the host [ 2 , 7 ]. The pathogen systematically deteriorates the immune function of the host by down-modulating overall activities and functioning of both macrophage and DC cell population [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation